Imagining identity in New Spain : race, lineage, and the colonial body in portraiture and casta paintings - Carrera, Magali Marie, 1950- (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2003)
Reacting to the rising numbers of mixed-blood (Spanish-Indian-Black African) people in its New Spain colony, the eighteenth-century Bourbon government of Spain attempted to categorize and control its colonial subjects through increasing social regulation of their bodies and the spaces they inhabited. The discourse of calidad (status) and raza (lineage) on which the regulations were based also found expression in the visual culture of New Spain, particularly in the unique genre of casta paintings, which purported to portray discrete categories of mixed-blood plebeians. Using an interdisciplinary approach that also considers legal, literary, and religious documents of the period, Magali Carrera focuses on eighteenth-century portraiture and casta paintings to understand how the people and spaces of New Spain were conceptualized and visualized. She explains how these visual practices emphasized a seeming realism that constructed colonial bodies--elite and non-elite--as knowable and visible. At the same time, however, she argues that the chaotic specificity of the lives and lived conditions in eighteenth-century New Spain belied the illusion of social orderliness and totality narrated in its visual art. Ultimately, she concludes, the inherent ambiguity of the colonial body and its spaces brought chaos to all dreams of order.